A Investigate On The Effect Of Language And Style On Understanding The Verses - Aydın, Hayati (Fırat University, 2022)
: This paper deals with the subject of mush?kala, ta'r?z, kin?ya and ij?z in terms of language andthe using of Qur’?n's verb and noun forms, human genre and adjective nouns in terms of style and someother related problems. The punishment or retribution from All?h (Makr) as mush?kala form, whichsometimes occurs at the level of a gradual diminution or collapse, is a punishment that gradually destroysthe sinner without his realizing it. However, it is possible to say that there is another dimension inMüsh?kala, destiny, and the formula of the working mechanism of destiny. According to this formula, it isunderstood that whatever behavior a person exhibits, Allah responds with a similar behavior. Based onthis dimension of destiny, it is understood that in one aspect (with the exception of Allah's will), mandetermines his own destiny relatively, and that his destiny is shaped as a result of his own actions. Some(Ta’r?d) verses and expressions with indirect narrative content were misinterpreted by some peoplebecause they implied something too deep to understand by human beings and had a profundity ofmeanings as well as secret wisdom. The fact is that about the 6th verse of the chapter of al-Mâida: "O youwho have believed, when you rise to (perform) prayer, wash your faces and your fore arms to the elbowsand your heads too." Shiites misunderstand Ibn Abbas's statement pointed out as "I can find nothing butwiping the feet in Allah's book, but they did not accept anything but washing", and their anointing of theirfeet is due to such a misunderstanding. In the Qur’?n, indirect expression is used in places that mentionabout the adab of maram (private) affairs in marital relationships; and that which should not be saidopenly. With such a form of expression, the Qur’?n is descended upon human beings from Allah to beexpressed in indirect expressions in situations where it is not welcome to express clearly. In the same way,it can be said that when the Qur’?n mentions a negative situation, it refers to it with closed expressions,and It can also be said that it uses Kinâya as a politeness and courtesy style. However, in any case, thecustomary usage should not be ignored while giving meaning to the verse expressions with allusions. Inexpressions of the Qur’?n, ij?z is used extensively; It is possible to say that a large part of the ij?z is theeliminate of words in expressions. For this reason it should not be overlooked that in some verses thatare not understood, some part of it may be deleted for ij?z. In terms of the style of the Qur’?n in thearticle, there are important points in terms of rhetoric in the use of verb and noun form, which is one ofthe topics discussed.

Makale, dil açısından müşâkele, ta’rîz, kinâye ve icâzı, üslûp açısından da Kur’ân’ın fiil ve isim formlarını, beşeri teamülleri, sıfat İsimleri kullanması gibi konuları ve ilgili problemleri ele almaktadır. Bir müşâkele formu olan Allah’ın Mekr (Hilesi)i, hasmı (farkına varmaksızın) derece derece olumsuzluk ve helake götüren bir ceza olmaktadır. Ta'rîz içerikli bazı âyet ve ifadeler, ima yoluyla bir şeye işaret ettikleri ve gizli bir niyet taşıdıklarından yorumda sorun oluşturabilir. Kur’ân'da cinselliği çağrıştıran ve sözün açıkça söylenmemesi gereken yerlerde kinâye kullanılmış ve bu gibi yerlerde ifadelerin kinâye ile söylenmesinin ima edildiği düşünebilir. Aynı şekilde Kur’ân’ın olumsuz bir durumdan bahsettiğinde buna kapalı ifadelerle göndermede bulunduğu gibi kinâyeye bir kibarlık ve nezaket üslubu olarak müracaat ettiği de söylenebilir. Kur’ân ifadelerinde icâz yoğun bir şekilde kullanılmaktadır. Özellikle de Kur’ân’da icâzın iki türlüsü, icâz-ı kasr ve icâz-ı hazif vardır. En çok kullanılan icâz-ı hazfi anlamak için bağlama dikkat etmenin ve söz akışını takip etmenin lazım olduğunu söylemek mümkündür. Kur’ân’ın üslûbu açısından ise ele alınan konulardan biri olan fiil ve isim formunu kullanmasında belagat açısından önemli nükteler vardır. Bunlar Kur’ân anlatımına bir güzellik katmaktadır. Kur’ân beşerî teamülleri kullanmış ve bununla da gaybî hakikatleri aktarmıştır. Kur’ân'da sıfat isimlerinin kullanılması onun evrenselliği ve prototipi hedeflediği, bireylerden çok sıfatlara ve kişiliğe öncelik verdiği ifade edilebilir.
Dil ve Üslûp Özelliklerinin Ayetleri Anlama Etkisi Üzerine Bir İnceleme
Keywords: Religious Studies; Din Araştırmaları